2020
DOI: 10.21203/rs.2.20599/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The toxicity of lithium to human cardiomyocytes

Abstract: Background: Lithium is widely used in the electronic consumer market and electric vehicles and has a great contribution in the world economy, resulting in large quantities of lithium waste in the environment. Yangtze River basin is one of the most developed areas in China. However, the environment influence of lithium in the Yangtze River basin and its roles in cardiomyocytes has not yet been clarified.Results: Here we found that the concentration of lithium in the water environment is very high in Shanghai, a… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 27 publications
0
4
0
1
Order By: Relevance
“…7,8 This is the reason planet earth is being converted into a lithium dump slowly and gradually. 9,10 To deal with both problems i.e., hydrogen storage and lithium, a novel proton battery concept was proposed that could run both in electrolyser mode to produce hydrogen by splitting water and in fuel cell mode to give out electricity. 11,12 Li et al 13 suggested a copper fiber filled flow field, simulated the pressure and flow velocity inside the fuel cell, and calculated the optimal operating parameters and porosity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…7,8 This is the reason planet earth is being converted into a lithium dump slowly and gradually. 9,10 To deal with both problems i.e., hydrogen storage and lithium, a novel proton battery concept was proposed that could run both in electrolyser mode to produce hydrogen by splitting water and in fuel cell mode to give out electricity. 11,12 Li et al 13 suggested a copper fiber filled flow field, simulated the pressure and flow velocity inside the fuel cell, and calculated the optimal operating parameters and porosity.…”
Section: Introductionmentioning
confidence: 99%
“…Besides, recycling of lithium incurs higher cost compared to its mining and manufacturing of a new battery 7,8 . This is the reason planet earth is being converted into a lithium dump slowly and gradually 9,10 . To deal with both problems i.e., hydrogen storage and lithium, a novel proton battery concept was proposed that could run both in electrolyser mode to produce hydrogen by splitting water and in fuel cell mode to give out electricity 11,12 …”
Section: Introductionmentioning
confidence: 99%
“…In recent times cell phones have become part and parcel of daily life, worldwide. The cell phone use is dependent on Lithium batteries plus its connection with WiFi.Lithium batteries have been identified in research to contain potential risk to human health [18,19]. Several researchers consider Oxidative stress and lipid peroxidation as important factor in development of various diseases, and consequently antioxidant role is given considerable importancein the prophylaxis and treatment of these diseases especially, the effects of vitamin E, the most important lipophilic radical-scavenging antioxidant, have been extensively investigated [20,21].…”
Section: Introductionmentioning
confidence: 99%
“…The sensor network usually has numerous nodes that spread over a large area, and it takes a lot of work to change or charge batteries for each node, no matter whether the node is powered by a primary battery or secondary battery. In addition, the abandon of large amounts of batteries will cause serious environmental pollution [ 11 , 12 , 13 ]. As a result, the investigation of a power supply system that contains renewable energy has attracted many scholars′ attention, and it is a new trend to introduce multiple renewable energy types and converting mechanisms for improving performance [ 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%